Chlormethine gel in combination with other therapies for treatment of mycosis fungoides: a review with patient cases - Ardigò, Marco; Nikbakht, Neda; Teoli, Miriam; Gleason, Laura; Crisan, Liliana; Querfeld, Christiane (Frontiers in Medicine, 2024)
Topical chlormethine gel has been approved as monotherapy for treatment of adult patients with mycosis fungoides (MF), the most common form of cutaneous T-cell lymphoma. In clinical practice, chlormethine gel is often combined with other skin-directed or systemic therapies to optimize response and target recalcitrant lesions. Positive outcomes with combination regimens using chlormethine gel and topical corticosteroids, phototherapy, retinoids, methotrexate, or interferon-α have been reported in literature. However, there are no treatment guidelines on the use of combination regimens with chlormethine gel. To provide real-world evidence and guidance on the use of chlormethine gel combination regimens, several cases of patients treated with chlormethine gel combined with phototherapy (n=5), retinoids (n=16), or mogamulizumab (n=3) are presented. These different combination regimens showed promising results. Most patients had a complete or partial response following treatment and the combinations were well-tolerated over extended treatment periods. Patients receiving chlormethine gel with retinoids had long-term periods of remission, even after treatment discontinuation. Durations of response of up to 3 years were observed in these patients. This long-term disease control may be the result of disease-modifying effects of chlormethine. Previous studies have shown targeted reductions in malignant T-cell clones in patients treated with chlormethine gel as well as improved posttreatment responses. Further research is needed to determine the effectiveness and safety of combination treatment regimens with chlormethine gel and to assess the impact chlormethine gel has on disease control.